EKOLOGI KERA EKOR PANJANG (Macaca fascicularis): STUDI AKTIVITAS HARIAN DAN PREFERENSI HABITAT DI LEMBAH GEMBUL TUBAN - M. Bilal Awwaluddin; Riska Andriani; Annisa Rahmawati; Hesti Kurniahu (Prodi Biologi Universitas PGRI Ronggolawe, 2024)
This study investigates the ecology of the long-tailed macaque (Macaca fascicularis) with a focus on their daily activities and habitat preferences in the Gembul Valley, Semanding District, Tuban Regency. The research aims to comprehend the behavioral patterns of long-tailed macaques and their relationship with the surrounding environment. Direct observation methods, utilizing concentration points to record daily activities, and vegetation analysis as a habitat assessment for long-tailed macaques, were employed using the rapid assessment method. The research findings reveal that long-tailed macaques in the Gembul Valley, Tuban, exhibit diverse daily activity patterns involving feeding, playing, communication, and resting behaviors. Habitat survey analysis discloses the preferences of long-tailed macaques for specific tree species, elevations, and the availability of water sources. The inhabited habitat of long-tailed macaques includes secondary forests, cliffs, and rivers. The monkeys derive sustenance from five types of food, four of which are plant-based, and one originates from animals. Environments that provide excellent shelter and accessibility to a variety of food resources are more frequently utilized by long-tailed macaques in the Gembul Valley area, Tuban.